A Review of the Potential Health Benefits of Nigella sativa on Obesity and Its Associated Complications - Siti Hajar Adam; Izuddin Fahmy Abu; Datu Agasi Mohd Kamal; Ami Febriza; Mohd Izhar Ariff Mohd Kashim; Mohd Helmy Mokhtar (Plants, 2023)
Obesity has become a worldwide epidemic and its prevalence continues to increase at an alarming rate. It is considered a major risk factor for the development of several comorbidities, including type 2 diabetes, stroke, other cardiovascular diseases and even cancer. Conventional treatments for obesity, such as dietary interventions, exercise and pharmacotherapy, have proven to have limited effectiveness and are often associated with undesirable side effects. Therefore, there is a growing interest in exploring alternative therapeutic approaches. Nigella sativa (NS), a medicinal plant with multiple pharmacological properties, has gained attention due to its potential role in the treatment of obesity and its associated complications. The aim of this review is therefore to assess the effects of NS on obesity and its complications and to provide insights into the underlying mechanisms. From this review, NS appears to play a complementary or supportive role in the treatment of obesity and its complications. However, future studies are needed to verify the efficacy of NS in the treatment of obesity and its complications and to prove its safety so that it can be introduced in patients with obesity.